Digital Art and Design for a Sustainable Future: Innovation, Ethics, and Identity - Bilozub, Liudmyla; Volodymyr, Oleksyn; Osadchyi, Viktor; Diachenko, Alla; Bondarchuk, Yuliia (European Journal of Sustainable Development, 2025)
Digital technologies have played a revolutionary role in design and art, operating innately within it, automating creative processes, and empowering artists and how they reply to the audience. Artificial intelligence, 3D modelling, and virtual and augmented reality open new possibilities for creativity, but such phenomena call into question whether such works are authentic and copyright exists. The study aims to examine the role played by digital technologies in the modernity of creative processes and the creative industries. This research methodology is related to the detailed analysis of scientific sources, comparative analysis of the historical and modern design ways, statistical research of digital art development and peculiarities of using the latest technologies in craftsmanship. It is shown that generative design, UX/UI, digital painting, automated animation, 3D modelling and virtual reality significantly reduce the time for creating and personalising the content, which is actively using artificial intelligence. Digitisation of art gives birth to challenges like copyright, authenticity preservation of art, and ethical application of AI and so forth at the same time. The relevance of the work is to i) generate key trends and opportunities to apply digital creativity, which is relevant for artists, designers and digital content creators, and ii) researchers in the creative economy. Further research is needed to develop ethical standards for generative art, the use of VR/AR in museum spaces, and the legislation of AI-generated works. Keywords: digital design, artificial intelligence, 3D modelling, virtual reality, generative design, automation of the creative process, creative industries, digital art, UX/UI design, copyright in digital art.